Prenatal diagnosis and outcome of absent pulmonary valve syndrome: contemporary single‐center experience and review of the literature. (7th January 2013) - Wertaschnigg, D.; Jaeggi, M.; Chitayat, D.; Shannon, P.; Ryan, G.; Thompson, M.; Yoo, S. J.; Jaeggi, E.
ABSTRACT: Objective: To review the anomaly spectrum of prenatally detected absent pulmonary valve syndrome (APVS) and the outcome after diagnosis. Previous fetal studies reported survival rates of ≤ 25% for patients with intended postnatal care. Methods: Clinical data and echocardiograms of 12 cases with a fetal diagnosis of APVS between 2000 and 2010 were analyzed in this retrospective single‐center study. Collected parameters included: gestational age at referral, associated fetal abnormalities, cardiothoracic ratio, maximum diameters of pulmonary annulus and main and branch pulmonary arteries, ventricular dimensions and function as well as ventricular Doppler flows. Karyotyping included fluorescence in‐situ hybridization (FISH) analysis for microdeletion 22q11.2. Results: Median gestational age at diagnosis was 24 weeks. Three subtypes of APVS were observed: (1) with tetralogy of Fallot (TOF) and no arterial duct ( n = 10; 83%); (2) isolated, with a large arterial duct ( n = 1; 8%); and (3) with tricuspid atresia, right ventricular dysplasia and a restricted duct ( n = 1; 8%). The cardiothoracic ratio and pulmonary artery dimensions were increased in all cases. The karyotype was abnormal in 70% of fetuses with TOF and their mortality rate was significantly higher due to pregnancy termination ( n = 3) or perinatal demise ( n = 2) (hazard ratio, 5; 95% CI, 0.87−28.9; P = 0.015). Of seven live births with active postnatal care, six children (86%) were alive without residual respiratory symptoms at a median follow‐up of 4.7 (range, 2.1−10.6) years. Conclusion: Outcome after fetal diagnosis of APVS was significantly better in this study compared with those of previous fetal series, with a low mortality rate for actively managed patients.